2018
DOI: 10.1093/icesjms/fsx240
|View full text |Cite
|
Sign up to set email alerts
|

Estimating post-release mortality of European sea bass based on experimental angling

Abstract: European sea bass (Dicentrarchus labrax) is an important target species for recreational and commercial fisheries. In recent years, the spawning stock biomass has declined markedly in some areas, and strict management measures have been introduced. However, the development of appropriate stock assessment and fisheries management has been hampered by a lack of information on post-release mortality. This study investigated post-release mortality of sea bass captured with common recreational fishing gear under ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 76 publications
1
30
3
2
Order By: Relevance
“…The resulting RI scores were significantly different between seasons only for seabass and plaice, and were very low for catshark (less than 10% on average), followed by sole and seabass (around 20% on average), and around 38% for plaice and skates. Although the relationship between the scores and discard survival rate were not established, these results indicate that the vitality of these species was not strongly impacted by these apparently rather favorable fishing conditions (shallow bottoms, short air exposures, light catch weights), in accordance with most of the previous discard survival studies for catshark (Revill et al, 2005;Rodríguez-Cabello et al, 2005), skates (Depestele et al, 2014;Ellis et al, 2017;Enever et al, 2009;Mandelman et al, 2013), seabass (Lewin et al, 2018;Morfin et al, 2017b), plaice and sole (Depestele et al, 2014;Methling et al, 2017;Uhlmann et al, 2016). the difference between seasons was significant for a given trait, light grey for March and black for July, and otherwise coloured grey for both seasons.…”
Section: Reflexes and Injuries Analysissupporting
confidence: 87%
“…The resulting RI scores were significantly different between seasons only for seabass and plaice, and were very low for catshark (less than 10% on average), followed by sole and seabass (around 20% on average), and around 38% for plaice and skates. Although the relationship between the scores and discard survival rate were not established, these results indicate that the vitality of these species was not strongly impacted by these apparently rather favorable fishing conditions (shallow bottoms, short air exposures, light catch weights), in accordance with most of the previous discard survival studies for catshark (Revill et al, 2005;Rodríguez-Cabello et al, 2005), skates (Depestele et al, 2014;Ellis et al, 2017;Enever et al, 2009;Mandelman et al, 2013), seabass (Lewin et al, 2018;Morfin et al, 2017b), plaice and sole (Depestele et al, 2014;Methling et al, 2017;Uhlmann et al, 2016). the difference between seasons was significant for a given trait, light grey for March and black for July, and otherwise coloured grey for both seasons.…”
Section: Reflexes and Injuries Analysissupporting
confidence: 87%
“…Conversely, using mortality values derived from studies conducted under certain circumstances for discards by commercial fishing or releases by MRF may result in underestimation of catches as country-specific differences in fishing practices will cause different associated mortality rates (e.g. [ 39 , 49 ]). The impact of not taking into account gear type in MRF post-release mortality was likely to be larger in countries allowing static gears (e.g.…”
Section: 0 Resultsmentioning
confidence: 99%
“…A decline was found in the larger body size classes in all 30 species examined, including common recreational species like cod, pollack and ray species. Lower numbers of larger size classes could cause smaller, younger fish to be at greater risk of being caught which may reduce populations in the long term (Lewin et al, ). A reduced chance of catching highly desired large individuals may cause recreational fishers to lose interest in the sport, although research in the United States has suggested that this is not always the case (McClenachan, ).…”
Section: Body Sizementioning
confidence: 99%